2009
DOI: 10.1055/s-0028-1112153
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 4-Methylbenzylidene-camphor (4-MBC) during Embryonic and Fetal Development in the Neuroendocrine Regulation of Testicular Axis in Prepubertal and Peripubertal Male Rats

Abstract: 4-Methylbenzylidene-camphor (4-MBC), an UV-B ray filter, belongs to the endocrine disrupters involved with alterations in the reproductive axis. Our target was to study the effect of 4-MBC on the neuroendocrine parameters that regulate reproduction in prepubertal and peripubertal male rats, which received this disrupter during embryonic and fetal development. 4-MBC was administered (sc) to female rats since pregnancy onset in doses of 20, 100 and 500 mg/kg/day. The litters were sacrificed at 15 or 30 days old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
1
2
0
1
Order By: Relevance
“…Subcutaneous administration of high dosages (up to 500 mg/kg/day) during pregnancy and lactation altered the hypothalamic secretion of excitatory amino acids Glu and Asp in male offspring. These neurotransmitters play a role as stimulators of gonadal axis, thus the observed changes are consistent with alterations in sexual development of male offspring, affecting pre-pubertal stage, but stimulating the peri-pubertal stage [56] . In addition, 4-MBC has been reported to have an acetylcholinesterase (AChE) inhibitory activity.…”
Section: Organic Filterssupporting
confidence: 67%
See 1 more Smart Citation
“…Subcutaneous administration of high dosages (up to 500 mg/kg/day) during pregnancy and lactation altered the hypothalamic secretion of excitatory amino acids Glu and Asp in male offspring. These neurotransmitters play a role as stimulators of gonadal axis, thus the observed changes are consistent with alterations in sexual development of male offspring, affecting pre-pubertal stage, but stimulating the peri-pubertal stage [56] . In addition, 4-MBC has been reported to have an acetylcholinesterase (AChE) inhibitory activity.…”
Section: Organic Filterssupporting
confidence: 67%
“…Inhibited testicular axis in male offspring during the pre-pubertal stage and stimulated during peri-pubertal stage. [56] Danio rerio Embryos exposed in medium 68 h 1–50 μM Inhibited AChE activity, impaired early muscular and neuronal development. [57] Neuro-2a mouse neuroblastoma cell line 45 min 0.1–100 μM Inhibited AChE activity.…”
Section: Organic Filtersmentioning
confidence: 99%
“…Thus, it has been shown that exposure to MBC in developing rats affects the regulation of target estrogen gene (Mueller et al 2003;Durrer et al 2005;, interferes in a specific way with sexual gene expression in the brain (Maerkel et al 2005;Maerkel et al 2007;Carou et al 2008;Carou et al 2009a;Carou et al 2009b), influences the development of organs and the reproductive functions in males (Durrer et al 2007;Hofkamp et al 2008) and even promotes the growth of the prostate .…”
Section: Iii32 Undesired Side Effectsmentioning
confidence: 97%
“…In einer weiteren Studie an ovarektomierten Ratten wurden bei ähn-lich hohen Dosen ein erhöhter TSH-und ein erniedrigter T4-Spiegel sowie ein uneinheitlicher, nicht dosisabhängiger Effekt auf den T3-Spiegel festgestellt [42]. Subkutane Verabreichung von 2-20 mg/ (kg KG · d) an weibliche Ratten stimulierte die Freisetzung von FSH, LH und GnRH [43]; die subkutane Verabreichung von 20-500 mg/(kg KG · d) an trächtige Ratten beeinflusste das Hodengewicht sowie die Gonadotropinfreisetzung aus dem Hypothalamus [44,45]. In einer anderen Untersuchung zeigte 4-MBC nach einmaliger oraler Gabe von 500 bzw.…”
Section: Reproduktionstoxizitätunclassified